Lip Morphology Changes After First Premolar Extractions in Patients With Bimaxillary Protrusion in Durg Population: A Pilot Study - Dr. Aman Kumar; Dr. Tanuj Chaudhari; Dr. Pradeep Babu Kommi; Dr. Mohit Kathole; Dr. Srijit Chattopadhay; Dr. Srishti Hariharno (The Bioscan, 2025)
Aim: To determine lip morphology changes after first premolar extractions in patients with bimaxillary protrusion as ratios of hard and soft tissue changes. Materials and Methods: The sample consisted of pretreatment and posttreatment lateral cephalograms of 20 subjects with Class I bimaxillary protrusion who had undergone orthodontic treatment with four first premolars extraction and retraction of upper and lower incisors. Pre and post treatment lateral cephalograms were traced and superimposed by using SN 7˚ plane. Fourteen linear measurements were made. Statistical analysis was performed to analyse the co relation between the hard and soft tissue change by Pearson’s correlation. Results: Significant changes after treatment were found both in dental and lip analysis. The co-relation of hard tissue to soft tissue were derived. Conclusion: statistical analysis revealed that a 1 mm retraction of the incisor cervical point would produce a 0.5 mm retraction of lip. The predictability of this study may be helpful for the clinician in predicting the amount of change in profile of the patient post treatment, thus aiding in planning the treatment.